Subject choice and earnings of UK graduates - Arnaud Chevalier (Institute for the Study of Labor (IZA), 2011)
Using a survey of a cohort of UK graduates, linked to administrative data on higher education participation, this paper investigates the labour market attainment of recent graduates by subject of study. We document a large heterogeneity in the mean wages of graduates from different subjects and a considerably larger one within subject with individuals with the most favourable unobserved characteristics obtaining wages almost twice as large as those with the worst. Moreover, gender differences in wages within subjects are also large. We then simulate a graduate tax to calculate a willingness to pay - in form of tuition fees - to capture these subject wage premia.
urn:nbn:de:101:1-201104213158
Keywords: I22; J31; 330; graduate earnings; tuition fees; Absolventen; Berufswahl; Bildungsertrag; Lohnstruktur; Studienfinanzierung; Willingness to pay; Großbritannien